2009
DOI: 10.1186/1423-0127-16-94
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive actions of honokiol and magnolol on glutamatergic and inflammatory pain

Abstract: The antinociceptive effects of honokiol and magnolol, two major bioactive constituents of the bark of Magnolia officinalis, were investigated on animal paw licking responses and thermal hyperalgesia induced by glutamate receptor agonists including glutamate, N-methyl-D-aspartate (NMDA), and metabotropic glutamate 5 receptor (mGluR5) activator (RS)-2-chloro-5-hydroxyphenylglycine (CHPG), as well as inflammatory mediators such as substance P and prostaglandin E2 (PGE2) in mice. The actions of honokiol and magnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 33 publications
0
55
2
Order By: Relevance
“…However, there are unclear the active compounds of Atracylodis Rhizoma and Zizyphi Fructus in anti-inflammatory effects. Magnolol and 6-gingerol are reported the major ingredients of Magnoliae Cortex (Lin et al, , 2009) and Zingiberis Rhizoma (Funk et al, 2009;Lee et al, 2009), respectively. The major ingredients in Glycyrrhizae Radix are glycyrrhizin and liquiritin, these were shown to have anti-inflammatory effects (Kim et al, 2006;Yoshida et al, 2007;Menegazzi et al, 2008;Jayaprakasam et al, 2009;Schröfelbauer et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…However, there are unclear the active compounds of Atracylodis Rhizoma and Zizyphi Fructus in anti-inflammatory effects. Magnolol and 6-gingerol are reported the major ingredients of Magnoliae Cortex (Lin et al, , 2009) and Zingiberis Rhizoma (Funk et al, 2009;Lee et al, 2009), respectively. The major ingredients in Glycyrrhizae Radix are glycyrrhizin and liquiritin, these were shown to have anti-inflammatory effects (Kim et al, 2006;Yoshida et al, 2007;Menegazzi et al, 2008;Jayaprakasam et al, 2009;Schröfelbauer et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Consistently, magnolol can inhibit cation signals stimulated by excitatory amino acid, leading to an increase in seizure threshold [9] . Moreover, our studies further demonstrated that magnolol and its isomer could attenuate inflammatory and glutamatergic pain in animal models [8,10] . Thus, the ability of magnolol to ameliorate neurotoxicity may be attributed to its antioxidative and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 81%
“…The symptomatic relief of PD has been attributed to the relative compensation of glutamate hyperactivity, because apomorphine has been shown to enhance extracellular glutamate levels in the striatum of 6-OHDA-lesioned animals [36] . Importantly, our previous studies have demonstrated that magnolol can antagonize glutamate-and NMDA-induced cation dysregulation, neuronal damage, seizures, as well as nociception [7,9,10] . Thus it is suggested that the protective and restorative effects of subchronic magnolol on apomorphine-induced rotational behavior may be due to blockade of glutamatergic signaling after dopamine denervation in 6-OHDA-lesioned mice.…”
Section: Discussionmentioning
confidence: 99%
“…Anthraquinone derivatives including aloe-emodin, rhein and sennosides also showed anti-inflammatory effects (Ma et al, 2009). Magnolol and honokiol also inhibited the second phase in the formalin test by inhibition of glutamate receptors and suppression of inflammatory mediators including PGE2 (Lee et al, 2011;Li et al, 2007;Lin et al, 2009). It was reported that the compounds exhibited the effects by synergy like three compounds of rhein, magnolol and naringenin exerted combined anti-inflammatory effect in a tradition Chinese formula (Tseng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%